The tadpole of Odontophrynus barrio Cei, Ruiz, and Beçak, 1982 (Anura: Odontophrynidae): a comparison with the other tadpoles of the genus - González, Exequiel Elías (2014)
We describe the tadpole of Odontophrynus barrioi including external larval features, chondrocranial and cranial musculature, and compare it with the other species of the genus. Tadpoles of O. barrioi at stages 31–37 are about 52.46 mm long. The body is slightly depressed in lateral view and ovoid in dorsal view. Oral disc is emarginate laterally, anteroventral and small with a single row of marginal papillae, a single large dorsal gap, and labial tooth row formula 2(2)/3(1). Despite small interspecific variations, like different labial tooth row formulae, the general aspect of species is quite similar. Although poorly-known yet, the chondrocranium and cranial musculature display some variations within the genus